Competitive Heavy‐Atom Tunneling Reactions Controlled Through Electronic Effects - José P. L. Roque; Cláudio M. Nunes; Fumito Saito; Bastian Bernhardt; Rui Fausto; Peter R. Schreiner (ChemistryEurope)
Abstract Controlling QMT reactivity remains exceptionally challenging and largely unexplored, as it requires rationales distinctly different from those used for classical chemical reactivity. Herein, we investigated how QMT reactivity can be controlled using electronic substituent effects. Benzazirines, which have the exceptional feature to react via two competitive QMT pathways, were used as model compounds. Three novel derivatives with increasingly stronger electron‐donating substituents at C4 [R = OH, N(CH3)2, and N(CH2)4] were generated in argon matrices at 3 K. Remarkably, different QMT selectivities were observed in all benzazirines. As the electron‐donating strength of the substituent increases, the QMT ring‐opening to nitrene starts to compete with the QMT ring‐expansion to ketenimine, becoming the dominant process for the strongest electron‐donating substituent [N(CH2)4]. A theoretical analysis of the substituent effects on the QMT reactivity of benzazirines was performed and compared with the experimental data for these and other C4 derivatives. Overall, the results compellingly demonstrate how subtle changes in electronic effects can be used to fine‐tune QMT selectivity.